1994
DOI: 10.1159/000292468
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone-Binding Protein in Plasma Is Inversely Correlated to Placental Lactogen and Augmented with Increasing Body Mass Index in Healthy Pregnant Women and Women with Gestational Diabetes mellitus

Abstract: Pituitary growth hormone (GH), prolactin (PRL), placental lactogen (PL), insulin-like growth factor 1 (IGF-1) and GH-binding protein (GHBP) in plasma were determined in 12 women with gestational diabetes mellitus (GDM) and in 12 healthy pregnant women during a breakfast meal tolerance test. The women with GDM showed higher prepregnancy weight, body mass index (BMI), basal levels of glucose, insulin, and C peptide compared to the pregnant controls. No difference was found between the two groups in pituitary GH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…This association has also been observed in pregnancy [5,9,29], but interestingly, we observed that this association was lost in the third trimester, where GHBP levels decrease and the maternal BMI increase. The same tendency has been observed in normal individuals [9].…”
Section: Discussionsupporting
confidence: 77%
“…This association has also been observed in pregnancy [5,9,29], but interestingly, we observed that this association was lost in the third trimester, where GHBP levels decrease and the maternal BMI increase. The same tendency has been observed in normal individuals [9].…”
Section: Discussionsupporting
confidence: 77%
“…Placental GH [17] and hPL [23] control embryo growth, likely via the opposing actions of insulin and insulin-like growth factors, inducing IR in humans [24]. hPL and prolactin increase maternal food intake by inducing central leptin resistance [17].…”
Section: Healthy Pregnancy: Changes In Glucose Metabolism and Immune mentioning
confidence: 99%
“…A positive correlation to BMI is recorded in healthy adults [97,98,161,162], in obesity and underweight conditions [163][164][165][166][167][168], during pregnancy [169,170], and in children [150,[171][172][173][174]; in the elderly this association is less pronounced [144]. Application of more specific measures of body fat reveals a very strong positive correlation of GHBP levels to fat mass [150,162].…”
Section: Body Compositionmentioning
confidence: 99%
“…Placental GH is reported to correlate inversely to GHBP levels [203]. The relationship between GHBP and BMI is maintained during pregnancy, although the significance is less pronounced [169,170,202].…”
Section: Pregnancymentioning
confidence: 99%
See 1 more Smart Citation